2012
DOI: 10.1152/jn.00678.2011
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of neurons in the rostral ventromedial medulla by neurokinin-1 receptors

Abstract: The rostral ventromedial medulla (RVM) is part of descending circuitry that modulates nociceptive processing at the level of the spinal cord. RVM output can facilitate pain transmission under certain conditions such as inflammation, and thereby contribute to hyperalgesia. Evidence suggests that substance P and activation of neurokinin-1 (NK-1) receptors in the RVM are involved in descending facilitation of nociception. We showed previously that injection of NK-1 receptor antagonists into the RVM attenuated mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 75 publications
4
33
1
Order By: Relevance
“…Our behavioral studies showed that loss of these neurons in the RVM did not alter withdrawal responses to acute mechanical or thermal stimuli but decreased hyperalgesia produced by intraplantar injection of capsaicin or prolonged hind paw inflammation. These findings are consistent with earlier studies and provide additional evidence that neurons in the RVM that express NK-1Rs are part of descending circuitry that facilitates nociception (Pacharinsak et al, 2008; Hamity et al, 2010; Lagraize et al, 2010; Brink et al, 2012; Khasabov et al, 2012). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our behavioral studies showed that loss of these neurons in the RVM did not alter withdrawal responses to acute mechanical or thermal stimuli but decreased hyperalgesia produced by intraplantar injection of capsaicin or prolonged hind paw inflammation. These findings are consistent with earlier studies and provide additional evidence that neurons in the RVM that express NK-1Rs are part of descending circuitry that facilitates nociception (Pacharinsak et al, 2008; Hamity et al, 2010; Lagraize et al, 2010; Brink et al, 2012; Khasabov et al, 2012). …”
Section: Discussionsupporting
confidence: 92%
“…We also showed that sensitization of ON cells to cutaneous stimulation following capsaicin (Brink et al, 2012) or prolonged inflammation (Khasabov et al, 2012) was reduced by an NK-1R antagonist. Although these studies showed that activation of NK-1Rs can enhance activity of ON cells and thereby contribute to facilitation of nociceptive transmission, this approach has limitations to understanding the role of NK-1R expressing RVM neurons because NK-1Rs are only a part of neurochemical mechanisms that regulate activity of these neurons.…”
Section: Introductionmentioning
confidence: 84%
“…Using this approach, no increase in SubP content was observed on either side of the RVM four hours, four days, or two weeks after CFA treatment. This negative finding was not congruent with the results of earlier pharmacological (Pacharinsak et al, 2008; Hamity et al, 2010; Lagraize et al, 2010), electrophysiological (Budai et al, 2007; Zhang and Hammond, 2009; Brink et al, 2012) and neuroanatomical (Hamity et al, 2014) investigations whose results suggested that CFA treatment may increase SubP release. Measurements in tissue homogenates may not be able to detect small changes in content, changes that are confined to subsets of neurons or changes that occur in specific compartments such as axon terminals.…”
Section: Discussioncontrasting
confidence: 87%
“…The mechanisms by which it acts in the periphery and spinal cord to induce and maintain heat hyperalgesia and mechanical hypersensitivity after peripheral inflammatory injury are well characterized (see reviews by (Baranauskas and Nistri, 1998; Sandkuhler et al, 2000; Snijdelaar et al, 2000; Mantyh, 2002; Keeble and Brain, 2004; Seybold, 2009; Todd, 2010; Steinhoff et al, 2014). Our understanding of its actions within supraspinal nuclei that modulate the transmission of nociceptive information in the spinal cord continues to evolve, particularly with respect to its actions in the rostral ventromedial medulla (RVM) (Lagraize et al, 2010; Hahm et al, 2011; Brink et al, 2012; Khasabov and Simone, 2013; Hamity et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation